The study of social problems : seven perspectives. - Rubington, Earl, 1923-2010; Weinberg, Martin S., 1939- (New York : University Press, 2003)
This critically acclaimed book delineates seven sociological perspectives used to examine social problems - social pathology, social disorganization, value conflict, deviant behaviour, labelling, the critical perspective, and, new to the sixth edition, social constructionism. Unlike most introductory texts for courses on social problems which are organized topically around issues such as drug abuse, racial violence, and juvenile delinquency, this anthology focuses on the major theoretical perspectives used to examine social problems. Each section begins with an overview of the main contributors to the perspective, its history, and an outline of its major characteristics, and closes with a critique of the perspective and questions for discussion. Long a standard in its field, The Study of Social Problems is an indispensable volume for building a strong theoretical foundation in courses on social problems
Inhoudsopgave : I. THE PROBLEM 1 Social Problems and Sociology. The Definition of a Social
Problem The Development of American Sociology Sociological Perspectives on Social Problems Plan of the Book Summary and Conclusion Selected References II. THE PERSPECTIVES 2 Social Pathology. The Concept of Social Problems Roots of the Social Pathology Perspective Changes in the Social Pathology Perspective Characteristics of the Social Pathology Perspective Summary and Conclusion The Organic Analogy The Criminal as a Born Criminal Type The Child Savers A Universal Criterion of Pathology The Pursuit of Loneliness The Moral Premises of Social Pathology Questions for Discussion Selected References 3 Social Disorganization. Problems of Society Problems of Discipline Differences Between the Pathology and the Disorganization Perspectives The Major Social Disorganization Theorists Characteristics of the Social Disorganization Perspectives Summary and Conclusion Social Change and Social Disorganization The Ecology of Urban Disorganization Family Disorganization The Decline of a Black Community Discussion
Selected References 4 Value Conflict. Conflict Theorists and the Formulation of the Value Conflict Perspective Characteristics of the Value Conflict Perspective Summary and Conclusion The Conflict of Values The Stages of a Social Problem Values, Politics, and Social Problems Words Without Deeds A Critique of the Value Conflict Perspective Questions for Discussion Selected References 5 Deviant Behavior. The Refocusing of Sociological Thought Roots in Classical Theory The Development of Anomie Theory The Development of Differential Association Theory Characteristics of the Deviant Behavior Perspective Summary and Conclusion Anomie and Social Structure A Theory of White Collar Crime Anomie: Theory and Fact An Evaluation of the Theory of Differential Association Questions for Discussion Selected References 6 Labeling. Focus and Concerns of the Labeling Perspective The Discipline and Its Problems Philosophical Sources of the Labeling Perspective Founders of the Labeling Perspective Characteristics of the
Labeling Perspective Summary and Conclusions Outsiders Primary and Secondary Deviation The Devaluation of Women The Saints and the Roughnecks A Critique of Labeling Questions for Discussion Selected References 7 Critical Perspective. The Main Idea of the Critical Perspective The Social Sources of the Critical Perspective Characteristics of the Critical Perspective Summary and Conclusion Crime and the Development of Capitalism Toward a Political Economy of Crime Repression and Criminal Justice in Capitalist America The Universalization of Social Problems Evaluating the Critical Perspective Questions for Discussion Selected References 8 Social Constructionism. The Labeling Perspective: The Critique from Outside The Rise of Social Constructionism Constructionism's Growth, Development, and Change Characteristics of the Constructionist Perspective Summary and Conclusion The Definition of Social Problems, John I. Kitsuse and Malcolm Spector How to Successfully Construct a Social Problem Victimization and
The Victim Industry Culture and the Case of Child Sexual Abuse Constructionism in Context Questions for Discussion Selected References III. THE PROSPECTS 9 A Sociological review of the Perspectives. The Seven Perspectives Applicability The Dual Mandate and Sociological Perspectives Society, Sociology, and the Study of Social Problems Questions for Discussion Selected References
Keywords: Sociologie